Peningkatan Ekonomi Pesantren melalui Pemberdayaan Usaha Kecil Menengah (UMKM) Toko Kitab (Studi Pondok Pesantren Sunan Darajat Banjarwati-Paciran-Lamongan) - Wilda ‘Ainun Najihah (Program Studi Ekonomi Syariah dengan Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2022)
Recently, Islamic boarding schools, one of the educational institutions, have begun to apply the methodology of building character (character building), bringing fresh air to the community. Not only transferring knowledge (transfer of knowledge) but equipping students and students to be able to empower themselves and the surrounding community, not only from the education sector but also other sectors. The role of Islamic boarding schools must be able to develop individual (charcter building) students to build social groups that have strong potential in filling the development of this country. Islamic boarding schools in Indonesia have started practicing skills education. The aim is to find out the Islamic boarding school-based economic empowerment, to know the supporting and inhibiting factors of Islamic boarding school-based economic empowerment. In this study, researchers used descriptive qualitative research methods, namely research methods based on post-positivism philosophy. Economic empowerment provides all books and students' books. Supporting Factors for Empowerment Procurement of self-printed books so that the costs are lower but you still get benefits because there are no intermediaries so that the selling prices are also affordable.